Comparison of different format of 15-sec intermittent exercises in youth soccer players - with a special reference to the physiological impact - Chardon, F. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The ability to repeat high intensity actions is an essential characteristic in elite soccer. In this context, intermittent exercises (i.e. 15-15-sec) are commonly used in order to improve this capacity but there is not a consensus of their characteristics, especially in youth categories. Therefore, the aim of this study was to compare different type of 15-15-sec intermittent exercises and to examine their physiological impacts on elite young soccer players. Methods: Twelve U17 players (172.9±5.8 cm; 64.5±5.8 kg, HRmax: 198.6±7.9 bpm, MAS: 15.6±0.9 km.h-1) from the same elite team participated in this study. During a 5-a-week period of competitive season, players have performed according to their individual maximal aerobic speed (MAS) the following different format of 15-sec intermittent exercises during 2 blocks of 8 min with active recovery: 1) 15-15-sec in-line running at 115% of MAS; 2-3) 15-15-sec including 180° turns at 110% and 115% of MAS; 4) a 15-15-15-sec at 115% of MAS; and 5) 15-45-sec including in-line running at 115% of MAS and specific physical (footwork) and technical actions (with the ball) according to the playing position. Players were tested in the Vameval test, 30-15 intermittent fitness test (30-15IFT) and a repeated sprint ability (RSA) test before and after the 5-a-week period. Heart rate responses during the exercise (HRres), heart rate recovery (HRR) post-exercise and ratings of perceived exertion (RPE) were monitored during all the tests and intermittent exercises. Results: The intermittent exercise including 180°directional changes induced higher HRres responses and RPE values than during the others intermittent exercises (p<0.05). The lower HR responses, HRR and RPE values were observed during the 15-15-sec including the ball (p<0.001). Furthermore, the combination of the different format of intermittent exercises during the 5 weeks not improved the performance in the different tests (NS). Discussion: The present study revealed that the 15-sec intermittent exercises with directional changes allow to reach higher HR response and RPE in youth soccer players whereas it is was the opposite for the format including the ball. These greater physiological responses are probably due to this format including 180° turns induced a deceleration, a block and a re-acceleration, and therefore a greater peripheral and anaerobic solicitation. In conclusion, it is suggested that coaches could include and combine different format of 15-15-sec (in-line, with ball and including footwork exercises) without altering the physiological solicitation. However, coaches should pay a special attention to the format including 180° directional changes.